Highly Facet‐Dependent Photocatalytic Properties of Cu2O Crystals Established through the Formation of Au‐Decorated Cu2O Heterostructures. Issue 35 (29th July 2016) - Yuan, Guo‐Zhi; Hsia, Chi‐Fu; Lin, Zhen‐Wen; Chiang, Chieh; Chiang, Yun‐Wei; Huang, Michael H.
Abstract: This work confirms the presence of a large facet‐dependent photocatalytic activity of Cu2 O crystals through sparse deposition of gold particles on Cu2 O cubes, octahedra, and rhombic dodecahedra. Au‐decorated Cu2 O rhombic dodecahedra and octahedra showed greatly enhanced photodegradation rates of methyl orange resulting from a better separation of the photogenerated electrons and holes, with the rhombic dodecahedra giving the best efficiency. Au–Cu2 O core–shell rhombic dodecahedra also displayed a better photocatalytic activity than pristine rhombic dodecahedra. However, Au‐deposited Cu2 O cubes, pristine cubes, and Au‐deposited small nanocubes bound by entirely 100 facets are all photocatalytically inactive. X‐ray photoelectron spectra (XPS) showed identical copper peak positions for these Au‐decorated crystals. Remarkably, electron paramagnetic resonance (EPR) measurements indicated a higher production of hydroxyl radicals for the photoirradiated Cu2 O rhombic dodecahedra than for the octahedra, but no radicals were produced from photoirradiated Cu2 O cubes. The Cu2 O 100 face may present a high energy barrier through its large band edge bending and/or electrostatic repulsion, preventing charge carriers from reaching to this surface. The conventional photocatalysis model fails in this case. The facet‐dependent photocatalytic differences should be observable in other semiconductor systems whenever a photoinduced charge‐transfer process occurs across an interface. Abstract : Structure is the key : Whereas Au‐decorated Cu2 O octahedra and rhombic dodecahedra (RD) show enhanced photocatalytic activities compared to their pristine particles, small and large Au‐decorated Cu2 O cubes remain inactive. EPR measurements indicate a higher production of hydroxyl radicals for Cu2 O rhombic dodecahedra than for octahedra upon photoirradiation, but no radicals are produced from photoirradiated Cu2 O cubes (see figure).